1975
DOI: 10.1021/bi00693a014
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the doublet at 850 and 830 cm-1 in the Raman spectra of tyrosyl residues in proteins and certain model compounds

Abstract: The doublet at 850 and 830 cm-1 in the Raman spectra of proteins containing tyrosyl residues has been examined as to its origin and the relation of its components to the environment of the phenyl ring, the state of the phenolic hydroxyl group, and the conformation of the amino acid backbone. Raman spectral studies on numerous model molecules related to tyrosine, including certain deuterium derivatives, show that the doublet is due to Fermi resonance between the ring-breathing vibration and the overtone of an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
516
2

Year Published

1991
1991
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 589 publications
(552 citation statements)
references
References 34 publications
(12 reference statements)
34
516
2
Order By: Relevance
“…Siamwiza et al (1975) have shown that this doublet is due to the Fermi resonance between the ring symmetric stretching vibration and the overtone of the C-C and C-O stretching vibrations. It is well-known that the Raman intensity ratio I 850 /I 830 is an indicator of the tyrosine environment (Siamwiza et al, 1975). For a high ratio (I 850 /I 830 ) 2.5), the hydroxyl group of the tyrosine acts like an acceptor of strong hydrogen bonds.…”
Section: Infraredmentioning
confidence: 97%
“…Siamwiza et al (1975) have shown that this doublet is due to the Fermi resonance between the ring symmetric stretching vibration and the overtone of the C-C and C-O stretching vibrations. It is well-known that the Raman intensity ratio I 850 /I 830 is an indicator of the tyrosine environment (Siamwiza et al, 1975). For a high ratio (I 850 /I 830 ) 2.5), the hydroxyl group of the tyrosine acts like an acceptor of strong hydrogen bonds.…”
Section: Infraredmentioning
confidence: 97%
“…23 Since this doublet has been observed for a large number of parasubstituted benzenes with C 2v local symmetry, we carefully analysed this region for the thyroid hormones, especially T2 and T4.…”
Section: Vibrational Assignmentmentioning
confidence: 99%
“…The Raman spectrum of native CK in buffer (10 mM Tris-HCl, pH 7.8, and 10 mM MgCl 2 ) is shown in Figure 1. Line fitting of the Tyr doublet at 852 and 828 cm -1 yields an intensity ratio (peak height) I(852)/I(828) of 1.25, suggesting that Tyr acts as weak H-bond donor/acceptor (34). The Raman spectra around 900 cm -1 show basically two bands at ca.…”
Section: Resultsmentioning
confidence: 98%